2022
DOI: 10.1093/nar/gkac893
|View full text |Cite
|
Sign up to set email alerts
|

ChromLoops: a comprehensive database for specific protein-mediated chromatin loops in diverse organisms

Abstract: Chromatin loops (or chromatin interactions) are important elements of chromatin structures. Disruption of chromatin loops is associated with many diseases, such as cancer and polydactyly. A few methods, including ChIA-PET, HiChIP and PLAC-Seq, have been proposed to detect high-resolution, specific protein-mediated chromatin loops. With rapid progress in 3D genomic research, ChIA-PET, HiChIP and PLAC-Seq datasets continue to accumulate, and effective collection and processing for these datasets are urgently nee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 86 publications
0
6
0
Order By: Relevance
“…Assay for Transposase-Accessible Chromatin sequencing (ATAC-seq) and ChIP-seq of multiple histone modifications were derived from Cistrome Data Browser. Chromloops is a novel database that aggregates a large number of PLAC-seq, ChIA-PET, and HiChIP datasets, which are often used in studies of chromatin interaction regulation [ 26 ]. In this study, the ChIA-PET dataset of Homo sapiens HT-1197 was included and RAD21 was identified as a ChIP-seq marker.…”
Section: Methodsmentioning
confidence: 99%
“…Assay for Transposase-Accessible Chromatin sequencing (ATAC-seq) and ChIP-seq of multiple histone modifications were derived from Cistrome Data Browser. Chromloops is a novel database that aggregates a large number of PLAC-seq, ChIA-PET, and HiChIP datasets, which are often used in studies of chromatin interaction regulation [ 26 ]. In this study, the ChIA-PET dataset of Homo sapiens HT-1197 was included and RAD21 was identified as a ChIP-seq marker.…”
Section: Methodsmentioning
confidence: 99%
“…Several well‐established databases, such as ChromLoops 40 and 3DIV, 41 offer a wealth of information on chromatin interactions in various types of cancer. By combining chromatin interactions and DNA methylation information of enhancer regions, we anticipate the emergence of increasingly accurate DNA methylation biomarkers in the future.…”
Section: Discussionmentioning
confidence: 99%
“…[117,118] Selected recently published databases provide a platform to study chromatin interactions, regulations and organisations. Such Example is ChromLoops [119] [https://3dgenomics.hzau.edu.cn/chromloops],…”
Section: Exploring Nuclear Organization With 3c-based Methodsmentioning
confidence: 99%
“…[ 117,118 ] Selected recently published databases provide a platform to study chromatin interactions, regulations and organisations. Such Example is ChromLoops [ 119 ] [https://3dgenomics.hzau.edu.cn/chromloops], an integrated dataset for high‐quality chromatin loops from 1030 datasets across 366 samples from 13 species from ChIA‐PET, HiChIP and PLAC‐Seq datasets. HiChIPdb [ 120 ] [http://health.tsinghua.edu.cn/hichipdb/] contains more than 260 million HiChIP interactions from 200 HiChIP experiments for 208 cell type at variable 1/5/10/50 kb resolution processed by FitHiChIP [ 121 ] and Hichipper [ 122 ] computational pipeline for loop calling.…”
Section: Exploring Nuclear Organization With 3c‐based Methodsmentioning
confidence: 99%